COVID-19 and the impact on surgical training and education in Singapore. Issue 1 (January 2022) - Seow, Choon Sheong; Lomanto, Davide; Ooi, London Lucien
Abstract: The COVID-19 pandemic has affected surgical education and training significantly. The main impact to surgical residency training is the reduction in number of patients (in caseload and case mix) and the conversion of face-to-face meetings into virtual ones for CME and clinical governance-related events. Assessment of surgical residents by examination (namely the Joint Specialty Fellowship Examination with the College of Surgeons of Hong Kong and the Royal College of Surgeons of Edinburgh) was cancelled at the peak of the pandemic, with resumption after acceptable COVID compatible adjustment was made to the format. The migration of CME events into a web-based one has resulted in greater connectivity with more audience. The potential and challenges of virtual format in surgical education include strategy and resources for sustainability; choice of optimal model for effective learning and surgical skills acquisition. In a post-COVID world, the model of blended learning is likely to remain. Abstract : Surgical education; COVID-19: teleconference; Surgical assessment.